Overcoming Supply Chain Challenges with Entrepreneurship & Networking Skills - Ahmed Saad Ishtiaque; Mehdi Rajeb; Faisal Mohammad Shahriar (International Journal of Supply Chain Management, 2021)
ABSTRACTSupply Chain Management has been an iatrical part of the business world for as long as we can remember. As we move forward from the industrial revolution to the digital information era the importance of the supply chain process has become more and more vital for business sustainability. As the supply chain process of a business becomes more structured over time it incorporates not only process and efficiency, but it also relies on entrepreneurship and networking skills of the business operators. This chapter looks into the case of Bangladesh through an empirical study which was done on 4 growing sectors, namely Real Estate, Furniture and the IT sector. The research data is an attempt to shed some light into a gap in literature regarding supply chain process and how SC is used to tackle business challenges, from the perspective of a nation which has recently been announced as a developing nation.The primary research under consideration looks into four highly potential sectors of Bangladesh. The authors have chosen to go for face-to-face interviews of over 575 business owners/CEOs/Managing Directors to get a detailed perspective of the business challenges they face from their business inception till date and how they use their entrepreneurship skills and the power of networking to mitigate those challenges. The sampling technique chosen was stratified random sampling as there were four different industries with small medium and large companies, all of which have their own business dynamics. Multistage regression analysis was used to decipher the data and bring out a clear picture of how networking is used by these owners to build up their supply chain networks. The study identifies, that in the case of Bangladesh, despite the fact that there are not much institutional support, the courts system remaining a bottleneck due to a combination of red tape and hence not much enforcement of contracts and a shadow of corruption in every sector at every level driving up operational costs; businesses in Bangladesh have continued to expand relying on brand value reputation, reliance of professional networks, to some extent a competitive bidding process and the sheer determination and Entrepreneurs skills of Bangladeshi business owners. The success of certain industries are primarily due to the contribution of human capital where the business owners’ ability to give the business his or her life and make it a successful venture on communication and networking has propelled us towards a steady growth.Key Words: Networking, Entrepreneurship skills, Business Challenges